Modulation of N3 and N719 dye···TiO2 Interfacial Structures in Dye-Sensitized Solar Cells As Influenced by Dye Counter Ions, Dye Deprotonation Levels, and Sensitizing Solvent - Cole, Jacqueline M; Gong, Yun; McCree-Grey, Jonathan; Evans, Peter J; Holt, Stephen A (ACS applied energy materials, 2018)
The fabrication process for dye-sensitized solar cells (DSCs) is well-established; yet, reported reliabilities of DSC device photovoltaic properties have been the subject of widespread controversy. The fabrication process will naturally affect these device properties, wherein the most susceptible DSC device component is its working electrode, which comprises a dye···TiO2 interface. While various analytical chemistry methods have probed this fabrication process indirectly, the molecular structure of this interface has not been tracked with varying dye sensitization conditions, via any direct means. Little is thus known about how steric and electronic factors associated with dye counterions, dye deprotonation levels, and the choice of sensitizing solvent impact upon the nature by which the dye···TiO2 interfacial structure forms via self-assembly. This work employs X-ray reflectometry (XRR) in combination with density functional theory calculations to probe the structural nature of dye···TiO2 interfaces featuring the ruthenium-based dye cis-bis(isothiocyanato)bis(2,2′-bipyridyl-4,4′-dicarboxylato)ruthenium(II) (N3), and its doubly deprotonated derivative ditetrabutylammonium cis-bis(isothiocyanato)bis(2,2′-bipyridyl-4,4′-dicarboxylato)ruthenium(II) (N719). XRR measurements show that N3 and N719 dye···TiO2 interfaces, sensitized using the co-solvent MeCN:t-BuOH (1:1, v/v) exhibit the same preferred bidentate binding mode, although minor structural variations were observed owing to the co-adsorption of tetrabutylammonium counterions in the case of N719. Further XRR studies on N3-adsorbed TiO2 surfaces sensitized using different solvents, MeCN:t-BuOH (1:1, v/v), EtOH:t-BuOH (1:1, v/v), EtOH, and DMSO, showed that the nature of dye···TiO2 adsorption binding modes depends not only on the acidity of the N3-containing solutions, which dictate the dye deprotonation levels, but also on the steric nature of the sensitizing solvent.